The virtue ethics of Hume and Nietzsche - Swanton, Christine, 1947- (New directions in ethics ;, 2015)
Although contemporary development of virtue ethics has focused on Aristotle, other great thinkers in ethics - notably Hume and Nietzsche - also placed virtue at the center of their ethical theorizing. Moving away from ancient moral theorists, and subjectivist interpretations of Hume's and Nietzsche's thought that have reduced their impact in normative ethics, Swanton provides a fresh perspective on the ethics of both philosophers. Discussion of the moral philosophies of Hume and Nietzsche in turn leads Swanton to seek alternative versions of virtue ethics, particularly areas that have been neglected in the mainstream Aristotelian tradition. Swanton's aim is not to argue for a virtue ethics inspired by either Nietzsche or Hume, as opposed to one inspired by Aristotle. Rather, she explores other options for virtue ethics by interpreting Hume and Nietzsche as virtue ethicists and by suggesting possibilities for virtue ethics inspired by those thinkers.--Book Jacket.